The Role of Orthoptists in Refraction - Miriam L. Conway; Rakhee Shah; Elizabeth Chapman; Bruce J. W. Evans (British and Irish Orthoptic Journal)
Purpose: In 2022, the General Optical Council initiated a call for evidence concerning the Opticians Act. This consultation aimed to gather input and evidence relevant to potential modifications to the Opticians Act. One piece of research that was commissioned aimed to investigate the role of orthoptists in refraction. Method: We invited a range of eye care practitioners to participate in an online virtual focus group. Focus group discussions were audio-recorded, transcribed, and thematically analysed. Results: Two focus group discussions involving sixteen eye care professionals were completed. Findings confirm some orthoptists are already performing refraction tasks within the hospital eye service, primarily with young children using cycloplegic retinoscopy. Participants indicated that, at present, orthoptists refract on behalf of ophthalmologists who issue spectacle prescriptions based on the findings of the orthoptist’s refraction. Potential benefits of orthoptists undertaking refraction responsibilities were discussed including the ability to conduct retinoscopy in hospital paediatric clinics where services are in high demand and there is often a shortage of refraction appointments. This shift could lead to decreased NHS waiting times, fewer patient appointments, improved clinical decision-making, and facilitate the assessment of accommodative dysfunction. Overall, the group were positive towards orthoptists conducting refractions and issuing optical prescriptions but with specific conditions: limited to hospital settings, necessitating adequate postgraduate training, supervision by a hospital eye service consultant, and regular ocular health assessments. Conclusion: This study assessed the involvement of orthoptists in present and prospective refraction services, including their potential to legally issue optical prescriptions. The research outlined both the potential benefits and mitigating strategies to address concerns if orthoptists could issue optical prescriptions.